Lipid Biomarkers and Cardiometabolic Diseases: Critical Knowledge Gaps and Future Research Directions - Hyun Suk Yang (Metabolites)
The past decade has witnessed transformative changes in our understanding of various lipid or lipid-related biomarkers (Table 1) and their relationships with cardiometabolic diseases [...]